Cooperative roles of glucose and asparagine-linked glycosylation in T-type calcium channel expression - Lazniewska, Joanna; Rzhepetskyy, Yuriy; Zhang, Fang-Xiong; Zamponi, Gerald W; Weiss, Norbert (Pflügers Archiv, 2016)
T-type calcium channels are key contributors to neuronal physiology where they shape electrical activity of nerve cells and contribute to the release of neurotransmitters. Enhanced T-type channel expression has been causally linked to a number of pathological conditions including peripheral painful diabetic neuropathy. Recently, it was demonstrated that asparagine-linked glycosylation not only plays an essential role in regulating cell surface expression of Cav3.2 channels, but may also support glucose-dependent potentiation of T-type currents. However, the underlying mechanisms by which N-glycosylation and glucose levels modulate the expression of T-type channels remain elusive. In the present study, we show that site-specific N-glycosylation of Cav3.2 is essential to stabilize expression of the channel at the plasma membrane. In contrast, elevated external glucose concentration appears to potentiate intracellular forward trafficking of the channel to the cell surface, resulting in an increased steady-state expression of the channel protein at the plasma membrane. Collectively, our study indicates that glucose and N-glycosylation act in concert to control the expression of Cav3.2 channels, and that alteration of these mechanisms may contribute to the altered expression of T-type channels in pathological conditions.
Keywords: HEK293 buňky; posttranslační úpravy proteinů; transport proteinů; Humans; lidé; asparagin; Protein Transport; buněčná membrána; Glycosylation; Asparagine; glukosa; HEK293 Cells; Protein Processing, Post-Translational; Glucose; Calcium Channels, T-Type; glykosylace; Cell Membrane; vápníkové kanály - typ T